Inhibition of inducible nitric oxide synthase reduces renal ischemia/reperfusion injury - Chatterjee, PK (2015)
Background. Nitric oxide (NO), produced via inducible nitric oxide synthase (iNOS), is implicated in the pathophysiology of renal ischemia/reperfusion (I/R) injury. The aim of this study was to investigate the effects of the iNOS inhibitors L-N-6-(1-iminoethyl)lysine (L-NIL) and aminoethyl-isothiourea (AE-ITU) on (a) renal dysfunction and injury mediated by bilateral I/R of rat kidneys in vivo and (b) cytokine-stimulated NO production by primary cultures of rat proximal tubule (PT) cells. Methods. Male Wistar rats subjected to bilateral renal ischemia (45 min) followed by reperfusion (6 h). Rats were administered either L-NIL (3 mg/kg IV bolus 15 min prior to I/R followed by 1 mg/kg/h throughout I/R) or AE-ITU (1 mg/kg IV bolus 15 min prior to I/R followed by 1 mg/kg/h throughout I/R). Serum and urinary biochemical indicators of renal dysfunction and injury were measured; serum creatinine (S-Cr glomerular dysfunction), fractional excretion of Na+ (FENa tubular dysfunction), serum aspartate aminotransferase (sAST, I/R injury) and urinary N-acetyl-beta-D-glucosaminidase (uNAG, tubular injury). Additionally, renal sections were used for histological grading of renal injury and for immunological evidence of nitrotyrosine formation. Nitrate/nitrate levels in plasma were measured using the Griess assay and used as an indicator of NO production. Primary cultures of rat PT cells were incubated with interferon-gamma (IFN-gamma, 100 IU/mL) and lipopolysaccharide (LPS, 10 mug/mL) for 24 h, either in the absence or presence of increasing concentrations of L-NIL or AE-ITU (0.001 to I mmol/L) after which nitrite/nitrate levels were measured using the Griess assay. Results. L-NIL and AE-ITU significantly reduced the I/R-mediated increases in S-Cr, FENa, sAST and uNAG, indicating attenuation of I/R-mediated renal dysfunction and injury. Specifically, L-NIL and AE-ITU reduced the I/R-mediated glomerular and tubular dysfunction and biochemical and histological evidence of tubular injury. Both L-NIL and AE-ITU attenuated the plasma levels of nitrate (indicating reduced NO production) and the immunohistochemical evidence of the formation of nitrotyrosine. In vitro, L-NIL and AE-ITU both significantly reduced cytokine-stimulated NO production by primary cultures of rat PT cells in a dose-dependent manner. Conclusions. These results suggest that L-NIL and AE-ITU reduce the renal dysfunction and injury associated with I/R of the kidney, via inhibition of iNOS activity and subsequent reduction of NO (and peroxynitrite) generation. We propose that selective and specific inhibitors of NOS activity may be useful against the NO-mediated renal dysfunction and injury associated with I/R of the kidney.